Le Temps et les Temps : dans les littératures juives et chrétiennes au tournant de notre ère - Grappe, Christian.; Ingelaere, Jean-Claude. (Supplements to the Journal for the Study of Judaism, 2006)
This volume deals with calendar and liturgical times on the one hand. It discusses questions related to the establishment of the calendar and the observance of traditional and new feasts in Palestine and in the diaspora. On the other hand this book deals with the predetermined organization of the times. It considers the periodization of times and the idea of a revelation being carried out from one period to another; the irruption of the fixed Time and the concomitant representation of a recovery of the times; and the expectation of the last times. In particular, the texts from Qumran, the New Testament, and hellenistic Jewish literature are investigated, but older and more recent texts are taken into account as well.